Synthesis and optical properties of novel D–π–A–π–D type cationic cyclopentadienyliron complexes of arenes1. Issue 67 (24th July 2015) - Zhao, B. D.; Li, G. L.; Shi, Y. Z.; Zhang, H. Q.; Wang, T.
<x xml:space="preserve">Abstract</x> With the enlarged and annulated ICT conjugation systems, three new cationic cyclopentadienyliron complexes exhibited significantly better third-order NLO absorption properties than the commercial cyclopentadienyliron arene complexes I-261.